Darkly - Pessl, Marisha (New York : Delacorte Press, 2024)
When high schooler Arcadia unexpectedly secures the notorious game-maker's internship, she and the other interns become players in the most twisted game yet.
new ya book 2024 fall.
Ages 12 up.
Keywords: Internship programs -- Fiction; Games -- Fiction; Mystery and detective stories; Young adult fiction; Detective and mystery fiction; Novels; Thriller fiction; Detective fiction; Mystery fiction